Qualität 2030 Die umfassende Strategie für das Gesundheitswesen - Schrappe, Matthias (MWV Medizinisch Wissenschaftliche Verlagsgesellschaft, 2014)
Quality and security serve as a projection surface for a wide variety of problems in the German healthcare system. Sustainable objectives as the basis for the further development of quality assurance in Germany are not in sight, however, credibility and trust in instruments and terminology are lost. We continue to finance quantity instead of quality, sectoral foreclosure is about cooperation. For all legislative activities - a fundamental reform approach has not yet been identified. This is where quality comes in 2030 and proposes a regulatory framework for healthcare, in which quality and patient safety are the controlling factors. It is clearly formulated which basic reform approaches are necessary, which interventions (e.g. Pay for Performance) are necessary and how these can be introduced into the system without negative side effects. Quality 2030 also stands for a realistic time frame for implementing this paradigm shift; the work is the basis of argument and work for the necessary reforms.